Green premia are a challenge and an opportunity for climate policy design - Till Köveker; Olga Chiappinelli; Mats Kröger; Oliver Lösch; Karsten Neuhoff; Jörn C. Richstein; Xi Sun (Nature Climate Change, 2023)
Adjusting green public support programmes to green premiums can reduce public spending, yet this is challenged by uncertainty. Underfunding green technologies can delay the green transition, and overfunding them can increase transition costs. Both risks of under- and overfunding can be reduced using responsive adjustments.
Keywords: 330; Climate-change mitigation; climate-change policy; environmental economics